Case reportsFamilial multiple cutaneous and uterine leiomyomatosis. Case report - Duś, Monika (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Cutaneous leiomyomas are uncommon, benign tumours originating from the smooth muscles. They are pink-violet, red-brown or skin-coloured nodules with characteristic tenderness exacerbated by pressure, stress and temperature changes. They usually involve the extensor surfaces of the extremities and trunk. Multiple leiomyomas are mainly pilar leiomyomas. Familial leiomyomatosis is a genetically determined disease connected with uterine leiomyomas and known as multiple cutaneous and uterine leiomyomatosis (MCUL). In the paper the case of a 56-year-old woman with multiple cutaneous and uterine leiomyomatosis of the left shoulder and trunk with familial occurrence of similar skin changes is presented.